2020
DOI: 10.1101/2020.12.14.422551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinating the morphogenesis-differentiation balance by tweaking the cytokinin-gibberellin equilibrium

Abstract: Morphogenesis and differentiation are important stages in organ development and shape determination. However, how they are balanced and tuned during development is not fully understood. In the compound leaved tomato, an extended morphogenesis phase allows for the initiation of leaflets, resulting in the compound form. Maintaining a prolonged morphogenetic phase in early stages of compound-leaf development is dependent on delayed activity of several factors that promote differentiation, including CIN-TCP transc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Treatment with bacterial isolates increased the number of leaves produced ( Figure 3C ). We therefore chose to examine leaf development, which follows a predictable and well characterized program in S. lycopersicum M82 (Shani et al, 2010; Israeli et al, 2021), in depth. For this, we selected the B. megaterium isolate 4C, which consistently performed best in growth promotion assays we conducted ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment with bacterial isolates increased the number of leaves produced ( Figure 3C ). We therefore chose to examine leaf development, which follows a predictable and well characterized program in S. lycopersicum M82 (Shani et al, 2010; Israeli et al, 2021), in depth. For this, we selected the B. megaterium isolate 4C, which consistently performed best in growth promotion assays we conducted ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the effect of bacterial isolates on development, we next examined the expression of a variety of developmental genes. We chose genes related to boundary definition, which is important for organ initiation (Steiner et al, 2020; Bar et al, 2016), meristem maintenance, which is important for increased morphogenesis (Israeli et al, 2021), and, given the TCSv2 activation results, genes of the CK pathway. We found that the bacilli isolates exclusively activated CK pathway genes ( Figure 5A-E ), with B. megaterium 4C not surprisingly activating more CK pathway genes than B. pumilus R2E.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, it was shown that CK promotes cell proliferation and that reduced CK levels lead to a decrease in cell divisions and consequently to smaller organs (Holst et al, 2011). Moreover, a recent study revealed that a CK/GA balance is responsible for leaf complexity in tomato as it controls morphogenesis/differentiation switch (Israeli et al, 2021). Hence, it is also possible that CK signaling is partially impaired in the spy-3 mutant and as a consequence modifies the serration growth dynamics.…”
Section: Spy Is a Component Of The Boundary Domains Networkmentioning
confidence: 99%